Therapeutic advances in obesity management: an overview of the therapeutic interventions - Roomy, Moody Al; Hussain, Kainat; Behbehani, Hawraa M.; Abu-Farha, Jenna; Al-Harris, Rayan; Ambi, Aishwarya Mariam; Abdalla, Mohammed Altigani; Al-Mulla, Fahd; Abu-Farha, Mohamed; Abubaker, Jehad (Frontiers in Endocrinology, 2024)
Obesity has become a global epidemic in the modern world, significantly impacting the global healthcare economy. Lifestyle interventions remain the primary approach to managing obesity, with medical therapy considered a secondary option, often used in conjunction with lifestyle modifications. In recent years, there has been a proliferation of newer therapeutic agents, revolutionizing the treatment landscape for obesity. Notably, glucagon-like peptide-1 receptor agonists (GLP-1 RAs), such as semaglutide, liraglutide, and the recently approved dual GLP-1/GIP RAs agonist tirzepatide, have emerged as effective medications for managing obesity, resulting in significant weight loss. These agents not only promote weight reduction but also improve metabolic parameters, including lipid profiles, glucose levels, and central adiposity. On the other hand, bariatric surgery has demonstrated superior efficacy in achieving weight reduction and addressing overall metabolic imbalances. However, with ongoing technological advancements, there is an ongoing debate regarding whether personalized medicine, targeting specific components, will shape the future of developing novel therapeutic agents for obesity management.